A high-cycle fatigue energy dissipation accurate estimation method considering natural convection and radiation heat transfer. (September 2020) - Yang, Wenping; Guo, Xinglin; Guo, Qiang
Highlights: Infrared thermography methodology for HCF energy dissipation estimation. Convection and radiation for energy dissipation estimation are non-negligible. Energy dissipation accurate estimation model is verified with FEM simulation. Abstract: As a rapid fatigue performance estimation method, the accuracy of dissipated energy estimation by infrared thermography methodology seriously affects the prediction of fatigue parameters. An energy dissipation accurate estimation method considering natural convection and radiation is developed. Numerical simulation verifies the accuracy of the presented method, and natural convection and radiation account for a large proportion of energy dissipation estimation, which cannot be ignored. With the experimental results of FV520B stainless steel, the energy dissipations during the high-cycle fatigue process were estimated and verified. This work provides theoretical and experimental basis for accurate estimation of energy dissipation in high-cycle fatigue.